Improving validity of the trail making test with alphabet support - Waggestad, Therese Händel; Kirsebom, Bjørn Eivind; Strobel, Carsten; Wallin, Anders; Eckerström, Marie; Fladby, Tormod; Egeland, Jens (Frontiers in Psychology, 2023)
Objective: The Trail Making Test (TMT) is commonly used worldwide to evaluate cognitive decline and car driving ability. However, it has received critique for its dependence on the Latin alphabet and thus, the risk of misclassifying some participants. Alphabet support potentially increases test validity by avoiding misclassification of executive dysfunction in participants with dyslexia and those with insufficient automatization of the Latin alphabet. However, Alphabet support might render the test less sensitive to set-shifting, thus compromising the validity of the test. This study compares two versions of the TMT: with and without alphabet support. Methods: We compared the TMT-A, TMT-B, and TMT-B:A ratios in two independent normative samples with (n=220) and without (n=64) alphabet support using multiple regression analysis adjusted for age and education. The sample comprised Scandinavians aged 70–84 years. Alphabet support was included by adding the Latin alphabet A–L on top of the page on the TMT-B. We hypothesized that alphabet support would not change the TMT-B:A ratio. Results: After adjusting for age and years of education, there were no significant differences between the two samples in the TMT-A, TMT-B, or the ratio score (TMT-B:A). Conclusion: Our results suggest that the inclusion of alphabet support does not alter TMT’s ability to measure set-shifting in a sample of older Scandinavian adults.